Studying the molecular dynamics of deuterium molecules trapped inside a simple clathrate hydrate using high resolution Raman spectroscopy - Ibrahim, Mohamed Ibrahim Moussa (AUC Knowledge Fountain, 2014)
As the energy resources running out, scientists are trying to provide sustainable energy. They move toward the hydrogen economy although it has large technical difficulties that need to be solved. Hydrogen is considered as a clean fuel. Storing hydrogen using clathrate hydrates is one of the promising ways to provide required energy. The high hydrogen content in sII clathrate hydrate proposes some applications like replacing gasoline to fuel vehicles, using as a gas separation substance, and transporting some dangerous gases. In addition, clathrate hydrate is found in nature in huge amounts. Generally speaking, it is approximated that about 3000 billion tons of carbons of clathrate hydrates exist as a worldwide reserves. This large amount can replace usual fossil fuel like oil and coal, and be a new energy source. All what we need is to investigate these compounds and find the ways to make use of them. Clathrate hydrates are inclusion compounds, physically resembles ice, can trap a guest small non polar molecule behind walls made by water via confining the guest molecules by a definite structure. So, it isn’t a chemical storage but physical. From the historical point of view, it is thought that the hydrogen and its isotopes are very small to make clathrate compounds stable but, recently, it is used to build a simple cubic structure II with water molecules. Formation of clathrate hydrates depends on the applied high pressure, low temperature, and the guest molecule. In this research, a full detailed picture of deuterium clathrate hydtare including structure, occupancy number per cage, deuterium dynamics, and ortho-para conversion of deuterium inside the cages has been conducted. The storage of deuterium in clathrate hydrate has been tested, and basal concepts of enclathrated deuterium have been evaluated. Manifold cavity occupation and small inter-molecular separation are some new exciting aspects. The small cages of sII structure can contain one deuterium molecule which represents deuterium content of 1.0 wt%. Raman spectroscopy is an important tool to study the dynamics of the trapped deuterium and the occupancy of deuterium inside the cages of the clathrate hydrate. It shows the vibrational and rotational bands of deuterium molecules. In sII hydrates, we have two types of cages: small cages and large cages. Enclathrated deuterium at all cages vibrates at lower frequency than free gas phase. In addition, the single deuterium occupied cages vibrates at lower frequency than multiple deuterium occupied cages. Raman spectra was collected from many samples of in-situ prepared deuterium clathrate placed in a cell to see the formation of the clathrate structure and the changes occur while applying heating and quenching cycles. Analysis of the vibrational bands of different cages has been explored and calculations regarding average occupancy number have been done.